Systematized methods for the development of Product-Service Systems: a systematic literature review - Braga Junior, Antonio Erlindo (2021)
Research on implementation of Product-Service Systems (PSS) in manufacturing companies has grown steadily and many methods have been published. This paper aims to identify and analyses existing methods on the implementation of PSS through a systematic literature review, focusing on methods with information considered enough for effective application. It was identified 1716 papers published among January 2006 and December 2018. Forty-six methods were identified; of which only 5 met the criteria established in the research for practical application. There is no convergence in the literature for indication of a predominant method, or even a guide to select the appropriate method for the business context. The approaches, procedures and characteristics of the methods are equivalent. No predominance of some over the others, about better results or efficiency, was observed. Despite the large volume of information identified, there is a gap in the literature, which is the lack of papers that guides effectively to develop a PSS and with detailed information for implementation